2020
DOI: 10.1038/s41598-020-71809-x
|View full text |Cite
|
Sign up to set email alerts
|

Major QTL with pleiotropic effects controlling time of leaf budburst and flowering-related traits in walnut (Juglans regia L.)

Abstract: Breeding studies in walnut (Juglans regia L.) are usually time consuming due to the long juvenile period and therefore, this study aimed to determine markers associated with time of leaf budburst and flowering-related traits by performing a genome-wide association study (GWAS). We investigated genotypic variation and its association with time of leaf budburst and flowering-related traits in 188 walnut accessions. Phenotypic data was obtained from 13 different traits during 3 consecutive years. We used DArT-seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…This is possibly related to the temperate climate of the natural habitat of iron walnuts in southwest China, mainly in Yunnan province [ 23 , 24 ]. Walnut species are distributed and cultivated in widely diverse ecologically regions in different climate areas in the world [ 20 , 21 , 22 , 25 , 26 , 27 ]. Previous reports showed that CBFs activate many downstream genes, and ICE1 acts upstream to regulate CBFs, which increases cold stress in plants [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is possibly related to the temperate climate of the natural habitat of iron walnuts in southwest China, mainly in Yunnan province [ 23 , 24 ]. Walnut species are distributed and cultivated in widely diverse ecologically regions in different climate areas in the world [ 20 , 21 , 22 , 25 , 26 , 27 ]. Previous reports showed that CBFs activate many downstream genes, and ICE1 acts upstream to regulate CBFs, which increases cold stress in plants [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persian walnuts and iron walnuts are also used as timber tree species for their high-quality wood [ 20 , 21 , 23 ]. It is commonly known that the flowering and pollinating time of walnuts is in late spring [ 26 , 27 ]. However, there is a limitation for pollinating quality and walnut yield in temperate regions where temperatures can plunge rapidly in the period of late spring frost (cold shock), especially in northern areas [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, compared to the qualitative traits, the quantitative traits with polygenic control were more sensitive to local environmental conditions [ 6 ]. Previous studies also found that leaf budbursts and flowering habits in walnut were significantly influenced by the environment [ 53 ], as well as the pellicle color [ 8 ] and water-use efficiencies [ 54 ]. For this study, the sampling location Guizhou Province was situated in a low-latitude subtropical region on the Yunnan–Guizhou Plateau in China, which is home to a humid subtropical monsoon climate.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al reported that FER was a positive regulator of auxin-promoted growth, to suppress the abscisic acid (ABA) response through the activation of a negative ABI2 regulator of ABA signaling [ 67 ]. In another GWAS panel for walnut [ 53 ], the FER gene was identified as temporally mediating leaf budburst, reflecting its essential role in the regulation of walnut development.…”
Section: Discussionmentioning
confidence: 99%
“…sesquipedalis (L.) Verdc. is commonly known as asparagus bean, Chinese long bean, long-podded cowpea, pea bean, snake bean or yardlong bean, and is one of the horticultural plants belonging to the legume group which is very important with rich nutritional value [13]. Yardlong bean is also considered one of the most important vegetable crops in parts of Indonesia, Thailand, Philippines, Taiwan, and China [21].…”
Section: Introductionmentioning
confidence: 99%